Distribution of wild host plants of Xylella fastidiosa subsp. fastidiosa in Mexico - Oliva Hurtado, María Margarita; Téliz-Ortiz, Daniel; Ortega-Arenas, Laura Delia; Quezada-Salinas, Andrés (Instituto de Ecología, A.C., 2020)
Background and Aims: Xylella fastidiosa subsp. fastidiosa, the causal agent of Pierce’s disease, is a γ-proteobacterium, native to America and present in Mexico in wine-growing areas of the Valle de Guadalupe, Baja California, Parras de la Fuente, Coahuila and Ezequiel Montes in Querétaro. This pathogen has numerous hosts, in some of them without causing disease but representing an important source of inoculum, while in others, it causes decay, chlorosis, wilting and even death of the plant. Despite the potential damage it can cause, there are no reports of the quantification of losses, presence and distribution of hosts in Mexico, which is essential to develop management strategies. The objective of this work was to determine by means of Geographic Information Systems, the presence and regional and altitudinal distribution of host wild plants in Mexico.Methods: A base of 7695 georeferenced data of plants reported in the literature as hosts of X. fastidiosa subsp. fastidiosa obtained from herbalized specimens was developed. The information was analyzed using Geographic Information Systems to determine the distribution of species by state, physiographic regions, altitudinal, latitudinal, and longitudinal ranges.Key results: Twenty six reported wild plant species were identified as wild hosts of X. fastidiosa subsp. fastidiosa, widely distributed in the 32 states of the Mexican Republic. The largest number of sites with species presence was recorded in the states of Mexico, Veracruz, and Sonora. The plants inhabit an altitudinal gradient of 0 to 4146 m a.s.l. and are concentrated in the physiographic province of the Trans-Mexican Volcanic Belt.Conclusions: In Mexico, there are conditions for the development of species of wild host plants of X. fastidiosa subsp. fastidiosa, especially in the area of ​​transition of the Trans-Mexican Volcanic Belt, in the State of Mexico, Mexico City, Durango, Michoacán and Veracruz.